ASTHMA EXACERBATION IN CHILDREN : A SYSTEMATIC REVIEW - Stevenie, (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2023)
According to the definition provided by the Global Initiative for Asthma (GINA), asthma is a chronic inflammatory illness of the airways. This disorder involves the participation of a large number of cells, most notably mast cells, eosinophils, and T lymphocytes. People who are susceptible to the condition have frequent episodes of wheezing, chest tightness, shortness of breath, and coughing, typically late at night or first thing in the morning. These symptoms are typically related to extensive but variable airway blockage, which is at least partially reversible both on its own and with treatment. This obstruction can occur either spontaneously or as a result of treatment. A hyperreactive response of the airways to a variety of stimuli has also been linked to the inflammation. Wheezing is one of the most common symptoms. It is characterized by a high-pitched, whistling musical sound that is produced by turbulence in the airflow. The wheezing heard on the patient's dying breath is the least severe type. Wheezing does not occur during the most severe episodes due to the restriction of airflow that is connected with the narrowing of the airways and the tiredness of the respiratory muscles. A beta2 agonist, azithromycin, inhaled corticosteroids, and antimuscarinic may be recommended to patients under the age of 18 who are experiencing acute exacerbations of their asthma.